Wide Band‐Gap Bismuth‐based p‐Dopants for Opto‐Electronic Applications. Issue 35 (21st July 2016) - Pecqueur, Sébastien; Maltenberger, Anna; Petrukhina, Marina A.; Halik, Marcus; Jaeger, Arndt; Pentlehner, Dominik; Schmid, Günter
Abstract: Ten new efficient p‐dopants for conductivity doping of organic semiconductors for OLEDs are identified. The key advantage of the electrophilic tris(carboxylato) bismuth(III) compounds is the unique low absorption of the resulting doped layers which promotes the efficiency of OLED devices. The combination of these features with their low fabrication cost, volatility, and stability, make these materials very attractive as dopants in organic electronics. Abstract : Bi doping : Ten new efficient p‐dopants for conductivity doping of organic semiconductors for OLEDs are identified. The key advantage of the electrophilic tris(carboxylato)bismuth(III) compounds is the unique low absorption of the resulting doped layers. The combination of this feature with their low fabrication cost, volatility, and stability, make these materials very attractive as dopants in organic electronics.